Hookworm Infections and Sociodemographic Factors Associated With Female Reproductive Tract Infections in Rural Areas of the Central Region of Togo - Holali Ameyapoh, Adjoa; Katawa, Gnatoulma; Ritter, Manuel; Tchopba, Christèle Nguepou; Tchadié, Pélagie Edlom; Arndts, Kathrin; Kamassa, Hélène E.; Mazou, Bassimtou; Amessoudji, Oukoe M.; N’djao, Akawulu; Agoro, Sibabe; Vogelbusch, Celina; et al. (Frontiers in Microbiology, 2021)
Female reproductive tract infections (FRTIs) have huge impact on women's health including their reproductive health in rural areas. Infectious and non-infectious factors have been associated with the occurrence of these infections. This study aimed to investigate socio-demographic and helminth infections as factors associated with FRTIs in six (6) rural areas of the central region of Togo. A semi-structured questionnaire was used to collect socio-demographical information and parasitological assessments were used to diagnose helminth infections. Moreover, cytobacteriological examination of vaginal swabs was performed for diagnosis candidiasis and bacterial vaginosis (BV) and real-time PCR technology were used to determine sexually transmitted infections (STIs). Finally, logistic regression analysis was performed to assess the relationship and association of these factors to FRTIs. The prevalence of FRTIs was 82.3% including 74.38% of sexually transmitted diseases (STDs) (74.38%), BV (31.79%) and vulvovaginal candidiasis (9.85%). In detail, FRTIs were caused by bacteria such as Ureaplasma parvum (50%), Ureaplasma urealyticum (26.5%) and Mycoplasma hominis (17.5%) and viruses such us cytomegalovirus (5%), HPV52 (4.1%), HPV45 (3.59%) and HPV35 (3.08%). No cases of Haemophilus ducreyi, Treponema pallidum, Varicella-zoster virus (VZV) and HPV56 were observed. The use of condoms was a protective factor (aOR= 0.23; 95%CI [0.11-0.51]) and the use of contraceptive methods was a risk factor (aOR= 2.49; 95%CI [1.19-5.19]) for STDs. Risk of BV was lower among participants, who had a number of pregnancies superior to 4 (aOR= 0.27; 95%CI [0.11-0.65]). Furthermore, women who ever had paid intercourse where at high probability risk of vulvovaginal candidiasis (aOR= 18.85; 95%CI [1.36-259.68]). Interestingly, women who had helminth infections were at high risk of HPV infection (OR= 2.19; 95%CI [1.01-4.74]). This study highlighted risk factors associated with FRTIs whose control would help to reduce the incidence of these diseases. Health-care professionals could develop education and sensitization strategies based on these risk factors and anti-helminthic treatment concepts might be taken in consideration to minimize the risk of HPV infections.